Pentingnya Psikologi Pendidikan Bagi Pendidik - Zahra, Andina; Firdausi An Tasya, Mutiara; Alfiyalawati, Nia; Nasution, Fauziah (Faculty Of Education, 2024)
Educational psychology as a science that examines mental problems and a person's psychological activities in relation to education as interaction is a discipline that is quite important in examining problems that disturb or support students' souls in the learning process, so that by understanding students' mental states, teachers can regulate and try to find solutions. regarding this problem, so for this matter, a teacher should have comprehensive knowledge about educational psychology so that learning can take place effectively and directed